Eternal enigma. The woman in chronicles by Enrique Gómez Carrillo - Poláková, Dora (2022)
The article is dedicated to the journalistic texts of the Guatemalan Enrique Gómez Carrillo (1873- 1927), a cosmopolitan author, known as the “king of chroniclers”. The modernist chronicle is the genre that opens the door to the new, the other, the rare and, moreover, symbolizes the struggle between “high” literature and the fast and fleeting world of the newspaper, the tension between the laws of the market and the aristocratic concept of art. We focus on the image of women that Gómez Carrillo offers to the readers; his chronicles take us to different countries and environments, the centre of modernity and beauty being the French metropolis - it is there that the new is forged, the sanctuary of art, fashion and beauty. With the author, we also travel to other favorite environments of the time, especially the Orient. Gómez Carrillo is fascinated by Japan, especially the character of the geisha as the embodiment of feminine ambiguity, between angel and devil. The oriental woman with her enigmatic condition is closely related to the prototypes of the femme fatale: Salome, Cleopatra or Astarte, all of “oriental” origin. The article shows how this image of the feminine - although poetically beautiful - obeys the stereotypes of the time: woman as a decorative sex.